High Voltage Engineering Fundamentals - Technology - Applications - Küchler, Andreas (VDI-Buch,, 2018)
This book is based on the leading German reference book on high voltage engineering. It includes innovative insulation concepts, new physical knowledge and new insulating materials, emerging techniques for testing, measuring and diagnosis, as well as new fields of application, such as high voltage direct current (HVDC) transmission. It provides an excellent access to high voltage engineering - for engineers, experts and scientists, as well as for students. High voltage engineering is not only a key technology for a safe, economic and sustainable electricity supply, which has become one of the most important challenges for modern society. Furthermore, a broad spectrum of industrial applications of high voltage technologies is used in most of the innovative fields of engineering and science. The book comprehensively covers the contents ranging from electrical field stresses and dielectric strengths through dielectrics, materials and technologies to typical insulation systems for AC, DC and impulse stresses. Thereby, the book provides a unique and successful combination of scientific foundations, modern technologies and practical applications, and it is clearly illustrated by many figures, examples and exercises. Therefore, it is an essential tool both for teaching at universities and for the users of high voltage technologies. The author Professor Dr.-Ing. Andreas Küchler is institute director at the University of Applied Sciences Würzburg-Schweinfurt, Germany. His research interests include insulation systems for DC voltages, transformers and bushings as well as condition assessment of HV equipment and industrial applications of high voltages. Prof. Küchler graduated in Electrical Engineering from the University of Karlsruhe, and he was working on pulsed-power technology in cooperation with the Karlsruhe Research Center. Then he was R&D manager of F&G Hochspannungsgeräte Porz GmbH in Cologne with responsibility for the development of bushings, capacitors and HVDC insulation systems. At university, Prof. Küchler established the interdisciplinary research field "DC technologies" and he founded the Institute of Electrical Power Engineering and High Voltage Technology. Prof. Küchler is an active member of national and international working bodies such as VDE/ETG Q2 (Materials, Insulating Systems, Diagnostics) or CIGRÉ SC A2 (Transformers) and D1 (Materials and Emerging Test Techniques).